A high-frequency low-iron-loss soft magnetic composite material and preparation method thereof
By chemically generating multi-layer clad structures on the surface of soft magnetic particles, the problem of large power loss in existing soft magnetic composite materials under high frequency conditions is solved, and the preparation of high-frequency low iron loss soft magnetic composite materials is realized, improving the Its magnetic properties are reduced and production costs are reduced.
Patent Information
- Application Number
- CN202311004488.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-10
AI Technical Summary
The existing soft magnetic composite materials have large power losses under high frequency conditions, making it difficult to meet the needs of electronic equipment with high frequency, small integration, lightweight, and excellent DC superposition characteristics.
By chemically forming a multi-layer cladding structure on the surface of soft magnetic particles, the cladding layer is formed in step by using materials such as coupling agents, oxide precursors and phosphates to reduce the high-frequency loss of soft magnetic composite materials.
It effectively reduces the high-frequency loss of soft magnetic composite materials and improves its high-frequency magnetic properties. At the same time, it is simple in process and low in cost, making it suitable for industrial applications.
Smart Images

Figure CN117198673B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft magnetic composite material preparation, and in particular to a high-frequency low iron loss soft magnetic composite material and a preparation method thereof. Background Art
[0002] The rapid development of the power electronics industry has driven the demand for electronic devices with high frequency, small integration, light weight, and excellent DC superposition characteristics. This has led to a growing demand for power magnetic materials that can work under high-frequency transmission conditions, which is essential for advancing ultra-large-scale digital integrated circuits at high frequencies. Soft magnetic composite materials are an important component of integrated circuits and come in many forms, including FeSi, Mn-Zn ferrite, Fe-Si-BP-Cu, Fe-Si-B, Fe-Cu-Nb-Si-B, Fe-Si-Al, etc. According to the different properties of these magnetic powders, they are generally used in different fields. For example, Fe-Si-BP-Cu, Fe-Si-B, Fe-Cu-Nb-Si-B, Fe-Si-Al, and FeSi are mainly used in the cores of filters and power inductors. High permeability Mn-Zn ferrite materials are mainly used in electronic circuits in the fields of broadband transformers, pulse transformers, etc. With the continuous reduction in the size of digital integrated circuits and the continuous increase in frequency, soft magnetic composite materials face higher performance requirements. Summary of the invention
[0003] 1. Technical issues to be resolved
[0004] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a high-frequency, low iron loss soft magnetic composite material and a preparation method thereof, which chemically generates a surface coating layer in situ on the surface of soft magnetic particles. The high-frequency, low iron loss soft magnetic composite material prepared by this method can effectively reduce the high-frequency loss of the soft magnetic composite material.
[0005] (II) Technical solution
[0006] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0007] In a first aspect, an embodiment of the present invention provides a method for preparing a high-frequency, low iron loss soft magnetic composite material.
[0008] An embodiment of the present invention provides a method for preparing a high-frequency, low-iron-loss soft magnetic composite material, the method comprising:
[0009] After placing the iron-based soft magnetic powder and the coupling agent in anhydrous ethanol and stirring, the iron-based soft magnetic powder is separated and dried;
[0010] After placing the iron-based soft magnetic powder and the oxide precursor in deionized water and stirring, the iron-based soft magnetic powder is separated and dried to obtain an iron-based soft magnetic powder having a coupling agent coating layer and an oxide precursor coating layer;
[0011] The iron-based soft magnetic powder having the coupling agent coating layer and the oxide precursor coating layer is subjected to segmented annealing to obtain the iron-based soft magnetic powder having the coupling layer and the oxide coating layer;
[0012] The iron-based soft magnetic powder having a coupling layer and an oxide coating layer, a binder, phosphoric acid or a phosphate are placed in an acetone reagent, stirred, and then dried to obtain an iron-based soft magnetic powder having a multi-layer coating structure on the surface;
[0013] The iron-based soft magnetic powder with the multi-layer surface coating structure is pressed into shape, and is subjected to segmented annealing in a protective gas atmosphere to obtain a high-frequency and low-iron-loss soft magnetic composite material.
[0014] Furthermore, the annealing process route of the segmented annealing is: controlling the temperature at 200-300°C and keeping it warm for 30-60 minutes, adjusting the temperature at 300-450°C and keeping it warm for 30-60 minutes, then adjusting the temperature at 450-600°C and keeping it warm for 60-120 minutes, and then adjusting the temperature at 600-900°C and keeping it warm for 60-120 minutes.
[0015] Furthermore, the mass percentages of the iron-based soft magnetic powder, the coupling agent, the oxide precursor, the phosphate and the binder are: 1: (0.5% to 3%): (0.1% to 2%): (0.1% to 1%): (0.5% to 4%).
[0016] Furthermore, the mass percentages of the iron-based soft magnetic powder, the anhydrous ethanol and the deionized water are: 1: (10% to 20%): (50% to 200%).
[0017] Furthermore, the adhesive is one of modified silicone resin, epoxy resin, polyimide adhesive and polyurethane adhesive.
[0018] Furthermore, the iron-based soft magnetic powder is at least one of FeNi, FeSiB, FeSi, FeSiAl, FeSiNbBCu, FeSiCr and FeSiBCrC.
[0019] Furthermore, the oxide precursor is at least one of zirconium oxychloride, ferric oxide, sodium hydroxide, magnesium chloride and magnesium nitrate.
[0020] Furthermore, the coupling agent is at least one of DL602, KH792, KH550, and KH570.
[0021] Furthermore, the phosphate is one of sodium dihydrogen phosphate, aluminum dihydrogen phosphate, potassium dihydrogen phosphate, and calcium dihydrogen phosphate.
[0022] In a second aspect, an embodiment of the present invention provides a high-frequency, low iron loss soft magnetic composite material.
[0023] A high-frequency, low iron loss soft magnetic composite material provided in an embodiment of the present invention is prepared by the preparation method described in the first aspect above.
[0024] (III) Beneficial effects
[0025] The beneficial effects of the present invention are as follows: the present invention provides a high-frequency, low-iron-loss soft magnetic composite material and a preparation method thereof, wherein the method comprises the following steps: placing an iron-based soft magnetic powder and a coupling agent in anhydrous ethanol and stirring, separating the iron-based soft magnetic powder and drying; placing the iron-based soft magnetic powder and an oxide precursor in deionized water and stirring, separating the iron-based soft magnetic powder and drying, to obtain an iron-based soft magnetic powder having a coupling agent coating layer and an oxide precursor coating layer; performing segmented annealing on the iron-based soft magnetic powder having a coupling agent coating layer and an oxide precursor coating layer to obtain an iron-based soft magnetic powder having a coupling layer and an oxide coating layer; placing the iron-based soft magnetic powder having a coupling layer and an oxide coating layer, a binder, phosphoric acid or a phosphate in an acetone reagent and stirring, and then drying, to obtain an iron-based soft magnetic powder having a surface multilayer coating structure; pressing the iron-based soft magnetic powder having a surface multilayer coating structure into a mold, and performing segmented annealing in a protective gas atmosphere, to obtain a high-frequency, low-iron-loss soft magnetic composite material.
[0026] The method generates a surface coating layer on the surface of the soft magnetic particles in situ chemically. Specifically, the multilayer coating structure is formed step by step on the surface of the magnetic powder particles using a high resistivity oxide prepared by the chemical in situ generation method and other coating components. The coating layer formed by the chemical in situ method can effectively reduce the power loss of the soft magnetic composite material and further improve the high-frequency magnetic properties of the soft magnetic powder. In addition, the coating agent is a common chemical product available on the market, with low production cost, and the coating process is simple, without the need for special equipment and experimental environment. The experimental conditions are simple and the process steps are few, which is suitable for actual industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a process flow chart of a method for preparing a high-frequency, low iron loss soft magnetic composite material. DETAILED DESCRIPTION
[0028] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0029] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0030] In these embodiments, unless otherwise specified, the parts and percentages are all measured by mass. "Parts by mass" refers to the basic unit of measurement representing the mass ratio relationship of multiple components. 1 part can represent any unit mass, such as 1g, 3.527g, etc. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts. "And / or" is used to indicate that one or both of the situations described may occur, for example, A and / or B include (A and B) and (A or B).
[0031] refer to Figure 1 In the first aspect, an embodiment of the present invention provides a method for preparing a high-frequency, low iron loss soft magnetic composite material.
[0032] An embodiment of the present invention provides a method for preparing a high-frequency, low-iron-loss soft magnetic composite material, the method comprising:
[0033] Step 1: After placing the iron-based soft magnetic powder and the coupling agent in anhydrous ethanol and stirring, the iron-based soft magnetic powder is separated and dried;
[0034] For example, the iron-based soft magnetic powder and the coupling agent may be placed in anhydrous ethanol and stirred for 5 to 15 minutes, and then the magnetic powder may be magnetically separated and dried.
[0035] In the technical solution, the iron-based soft magnetic powder is at least one of FeNi, FeSiB, FeSi, FeSiAl, FeSiNbBCu, FeSiCr and FeSiBCrC.
[0036] In the technical solution, the coupling agent is at least one of DL602, KH792, KH550, and KH570.
[0037] Step 2: After placing the iron-based soft magnetic powder and the oxide precursor in deionized water and stirring, the iron-based soft magnetic powder is separated and dried to obtain the iron-based soft magnetic powder having a coupling agent coating layer and an oxide precursor coating layer;
[0038] For example, the iron-based soft magnetic powder, oxide precursor or oxide precursor generating reagent can be placed in deionized water at a temperature of 25° C. to 50° C., stirred for 10 to 20 minutes, and then the magnetic powder can be taken out by magnetic separation and dried.
[0039] In the technical solution, the oxide precursor is at least one of zirconium oxychloride, ferric oxide, sodium hydroxide, magnesium chloride and magnesium nitrate.
[0040] In the technical solution, the mass percentages of iron-based soft magnetic powder, anhydrous ethanol and deionized water are: 1: (10% to 20%): (50% to 200%).
[0041] Step 3: performing segmented annealing on the iron-based soft magnetic powder having the coupling agent coating layer and the oxide precursor coating layer to obtain the iron-based soft magnetic powder having the coupling layer and the oxide coating layer;
[0042] In the present technical scheme, the annealing process route of the staged annealing is: control the temperature at 200-300°C and keep it warm for 30-60 minutes, adjust the temperature at 300-450°C and keep it warm for 30-60 minutes, then adjust the temperature at 450-600°C and keep it warm for 60-120 minutes, and then adjust the temperature at 600-900°C and keep it warm for 60-120 minutes.
[0043] Step 4: placing the iron-based soft magnetic powder having a coupling layer and an oxide coating layer, a binder, phosphoric acid or a phosphate in an acetone reagent, stirring and drying to obtain an iron-based soft magnetic powder having a surface multi-layer coating structure;
[0044] For example, the iron-based soft magnetic powder, phosphoric acid / phosphate and a binder can be placed in an acetone reagent and stirred for 5 to 20 minutes, and the magnetic powder can be dried to obtain an iron-based soft magnetic powder with a multi-layer coating structure on the surface.
[0045] Exemplarily, the multilayer coating structure has a thickness of 10 to 200 nm.
[0046] In the technical solution, the adhesive is one of modified silicone resin, epoxy resin, polyimide adhesive and polyurethane adhesive.
[0047] In the present technical solution, the phosphate is one of sodium dihydrogen phosphate, aluminum dihydrogen phosphate, potassium dihydrogen phosphate, and calcium dihydrogen phosphate.
[0048] In the present technical solution, the mass percentages of the iron-based soft magnetic powder, coupling agent, oxide precursor, phosphate and binder are: 1: (0.5% to 3%): (0.1% to 2%): (0.1% to 1%): (0.5% to 4%).
[0049] Step 5: Press the iron-based soft magnetic powder with a multi-layer surface coating structure into a mold, and then perform segmented annealing in a protective gas atmosphere to obtain a high-frequency and low iron loss soft magnetic composite material.
[0050] In the present technical solution, the protective gas is at least one of high-purity nitrogen, high-purity argon, high-purity oxygen, high-purity hydrogen, and air.
[0051] A method for preparing a high-frequency, low-iron-loss soft magnetic composite material mentioned in the present application is to generate a coating layer on the surface of soft magnetic particles using a chemical in-situ generation method. Specifically, the coating layer is a high-resistivity oxide prepared by a chemical in-situ generation method and other coating components are formed step by step on the surface of magnetic powder particles, from the inside to the outside, respectively, an oxide layer, a phosphate layer, and a bonding layer. The coating layer formed by the chemical in-situ generation method can effectively reduce the power loss of the soft magnetic composite material and further improve the high-frequency magnetic properties of the soft magnetic powder. In addition, the coating agent is a common chemical product that can be bought on the market, with low production cost, and the coating process is simple, and no special equipment and experimental environment are required. The experimental conditions are simple and the process steps are few, which is suitable for actual industrial applications.
[0052] In a second aspect, an embodiment of the present invention provides a high-frequency, low iron loss soft magnetic composite material.
[0053] A high-frequency, low iron loss soft magnetic composite material proposed in an embodiment of the present invention is prepared by the preparation method of the first aspect mentioned above, and includes all the beneficial effects mentioned in the first aspect mentioned above, which will not be repeated here.
[0054] In order to better understand the above technical scheme, exemplary embodiments of the present invention will be described in more detail below. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a clearer and more thorough understanding of the present invention, and to be able to fully convey the scope of the present invention to those skilled in the art.
[0055] Example 1
[0056] Step S1: FeNi magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 10 min, and then magnetically separated and the magnetic powder is dried.
[0057] Step S2: Place FeNi magnetic powder and 0.2 wt % zirconium oxychloride in 100 wt % deionized water at 30° C., stir for 10 to 20 minutes, take out the magnetic powder by magnetic separation and dry it to obtain FeNi magnetic powder with a coupling agent coating layer and a zirconium dioxide precursor coating layer.
[0058] Step S3: annealing the FeNi magnetic powder to obtain FeNi magnetic powder with a coupling layer and a zirconium dioxide coating layer. The annealing process route is to first keep the temperature at 300°C for 30 minutes, then keep the temperature at 450°C for 60 minutes, then keep the temperature at 600°C for 120 minutes, and then keep the temperature at 900°C for 120 minutes. High-purity nitrogen is used as the protective gas atmosphere.
[0059] Step S4: FeNi magnetic powder, 0.2 wt % phosphoric acid and 2 wt % modified silicone resin are placed in acetone reagent respectively, stirred for 10 min and the magnetic powder is dried to obtain FeNi magnetic powder with a multi-layer coating structure on the surface.
[0060] Step S5: Pressing the FeNi magnetic powder with a multi-layer surface coating structure into a mold and performing segmented annealing to obtain a high-frequency, low-iron-loss soft magnetic composite material. The molding pressure is set to 1500 MPa, and the annealing process route is firstly to keep the temperature at 300°C for 30 minutes, then to keep the temperature at 450°C for 30 minutes, then to keep the temperature at 600°C for 60 minutes, and then to keep the temperature at 700°C for 120 minutes.
[0061] Example 2
[0062] The present embodiment is characterized in that it is different from the embodiment 1 in that the content of zirconium oxychloride is 0.4 wt %.
[0063] Example 3
[0064] The present embodiment is characterized in that it is different from the embodiment 1 in that the content of zirconium oxychloride is 0.6 wt %.
[0065] Example 4
[0066] The present embodiment is different from the embodiment 1 in that the content of zirconium oxychloride is 0.8 wt %.
[0067] Example 5
[0068] The present embodiment is characterized in that it is different from the embodiment 1 in that the content of zirconium oxychloride is 1 wt %.
[0069] Comparative Example 1
[0070] Step S1: FeNi magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 10 min, and then magnetically separated and the magnetic powder is dried.
[0071] Step S2: annealing the FeNi magnetic powder. The annealing process route is to first keep the temperature at 300°C for 30 minutes, then keep the temperature at 450°C for 60 minutes, then keep the temperature at 600°C for 120 minutes, and then keep the temperature at 900°C for 120 minutes. The protective gas atmosphere uses high-purity nitrogen.
[0072] Step S3: FeNi magnetic powder, 0.2 wt% phosphoric acid and 2 wt% modified silicone resin are placed in acetone reagent respectively, stirred for 10 min and the magnetic powder is dried to obtain FeNi magnetic powder with a multi-layer coating structure on the surface.
[0073] Step S4: Pressing the FeNi magnetic powder with the multi-layer surface coating structure into a shape and performing segmented annealing to obtain an iron-based soft magnetic composite material. The molding pressure is set to 1500 MPa, and the annealing process route is firstly to keep the temperature at 300°C for 30 minutes, then to keep the temperature at 450°C for 30 minutes, then to keep the temperature at 600°C for 60 minutes, and then to keep the temperature at 700°C for 120 minutes.
[0074] Among them, the loss and magnetic permeability of the high-frequency, low iron loss soft magnetic composite materials prepared in Examples 1 to 5 and Comparative Example 1 are shown in Table 1.
[0075]
[0076] Table 1
[0077] Example 6
[0078] Step S1: FeSi magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 10 min, and then magnetically separated and the magnetic powder is dried.
[0079] Step S2: annealing the FeSi magnetic powder in step S1 to obtain FeSi magnetic powder with a ferric oxide coating layer, wherein the content of ferric oxide is 0.2 wt %. The annealing process is to first keep the temperature at 300° C. for 120 minn, and the protective gas atmosphere is air.
[0080] Step S3: annealing the FeSi magnetic powder in step S2 to obtain FeSi magnetic powder coated with ferroferric oxide. The annealing process is to first keep the temperature at 200°C for 30 to 60 minutes, and then keep the temperature at 350°C for 120 minutes. The protective gas atmosphere uses a mixed gas of high-purity nitrogen and high-purity hydrogen.
[0081] Step S4: The FeSi magnetic powder, 0.2 wt% phosphoric acid and 2 wt% modified silicone resin in step S3 are placed in acetone reagent, stirred for 10 min and the magnetic powder is dried to obtain FeSi magnetic powder with a multi-layer coating structure on the surface.
[0082] Step S5: The FeSi magnetic powder with a multi-layer surface coating structure in step S4 is pressed into shape and subjected to segmented annealing to obtain a high-frequency, low iron loss soft magnetic composite material. The molding pressure is set to 1500 MPa, and the annealing process route is firstly kept at 300°C for 60 minutes, then kept at 450°C for 60 minutes, then kept at 600°C for 60 minutes, and then kept at 700°C for 60 minutes.
[0083] Example 7
[0084] In this embodiment, the feature different from that of Embodiment 6 is that the content of ferric oxide is 0.4 wt %.
[0085] Example 8
[0086] In this embodiment, the feature different from that of Embodiment 6 is that the content of ferric oxide is 0.6 wt %.
[0087] Example 9
[0088] In this embodiment, the feature different from that of Embodiment 6 is that the content of ferric oxide is 0.8 wt %.
[0089] Example 10
[0090] In this embodiment, the feature different from that of Embodiment 6 is that the content of ferric oxide is 1 wt %.
[0091] Comparative Example 2
[0092] Step S1: FeSi magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 10 min, and then magnetically separated and the magnetic powder is dried.
[0093] Step S2: annealing the FeSi magnetic powder. The annealing process is to first keep the temperature at 200°C for 30 to 60 minutes, and then keep the temperature at 350°C for 120 minutes. The protective gas atmosphere uses a mixed gas of high-purity nitrogen and high-purity hydrogen.
[0094] Step S3: FeSi magnetic powder, 0.2 wt% phosphoric acid and 2 wt% modified silicone resin are placed in acetone reagent respectively, stirred for 10 min and the magnetic powder is dried to obtain FeSi magnetic powder with a multi-layer coating structure on the surface.
[0095] Step S4: Pressing the FeSi magnetic powder with the multi-layer surface coating structure into a shape and performing segmented annealing to obtain an iron-based soft magnetic composite material. The molding pressure is set to 1500 MPa, and the annealing process route is firstly to keep the temperature at 300°C for 60 minutes, then to keep the temperature at 450°C for 60 minutes, then to keep the temperature at 600°C for 60 minutes, and then to keep the temperature at 700°C for 60 minutes.
[0096] Among them, the loss and magnetic permeability of the high-frequency low-iron soft magnetic composite materials prepared in Examples 6 to 10 and Comparative Example 2 are shown in Table 2.
[0097]
[0098] Table 2
[0099] Embodiment 11
[0100] Step S1: FeSiNbBCu magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 10 min, and then magnetically separated and dried.
[0101] Step S2: The FeSiNbBCu magnetic powder, sodium hydroxide and magnesium chloride in step S1 are placed in 100wt% deionized water at a temperature of 25°C, wherein the total content of sodium hydroxide and magnesium chloride is 0.1wt%. After stirring for 10 to 20 minutes, the magnetic powder is taken out by magnetic separation and dried to obtain FeSiNbBCu magnetic powder with a coupling agent coating layer and a magnesium hydroxide coating layer.
[0102] Step S3: annealing the FeSiNbBCu magnetic powder in step S2 to obtain FeSiNbBCu magnetic powder with a magnesium oxide coating. The annealing process is to first keep the temperature at 400°C for 60 minutes and then keep the temperature at 500°C for 120 minutes. High-purity nitrogen is used as the protective gas atmosphere.
[0103] Step S4: Place the FeSiNbBCu magnetic powder, 0.2wt% phosphoric acid and 2wt% modified silicone resin in acetone reagent, stir for 10 minutes and dry the magnetic powder to obtain FeSiNbBCu magnetic powder with a multi-layer coating structure on the surface.
[0104] Step S5: The FeSiNbBCu magnetic powder with a multi-layer surface coating structure in step S4 is pressed into shape and subjected to segmented annealing to obtain a high-frequency, low iron loss soft magnetic composite material. The molding pressure is set to 600 MPa, and the annealing process route is to keep the temperature at 200° C. for 120 minutes.
[0105] Example 12
[0106] In this embodiment, the feature different from that of Embodiment 11 is that the total content of sodium hydroxide and magnesium chloride is 0.3 wt %.
[0107] Embodiment 13
[0108] In this embodiment, the feature different from that of Embodiment 11 is that the total content of sodium hydroxide and magnesium chloride is 0.5 wt %.
[0109] Embodiment 14
[0110] In this embodiment, the feature different from that of Embodiment 11 is that the total content of sodium hydroxide and magnesium chloride is 0.7 wt %.
[0111] Embodiment 15
[0112] In this embodiment, the feature different from that of Embodiment 11 is that the total content of sodium hydroxide and magnesium chloride is 1 wt %.
[0113] Comparative Example 3
[0114] Step S1: FeSiNbBCu magnetic powder and 1 wt% coupling agent are placed in 10 wt% anhydrous ethanol and stirred for 10 min, and then magnetically separated and dried.
[0115] Step S2: annealing the FeSiNbBCu magnetic powder in step S1. The annealing process is to first keep the temperature at 400°C for 60 minutes and then keep the temperature at 500°C for 120 minutes. The protective gas atmosphere uses high-purity nitrogen.
[0116] Step S3: Place the FeSiNbBCu magnetic powder, 0.2wt% phosphoric acid and 2wt% modified silicone resin in acetone reagent respectively, stir for 10 minutes and dry the magnetic powder to obtain FeSiNbBCu magnetic powder with a multi-layer coating structure on the surface.
[0117] Step S4: The FeSiNbBCu magnetic powder with a multi-layer surface coating structure in step S3 is pressed into shape and subjected to segmented annealing to obtain an iron-based soft magnetic composite material. The molding pressure is set to 600 MPa, and the annealing process route is to keep the temperature at 200° C. for 120 minutes.
[0118] Among them, the loss and magnetic permeability of the high-frequency low-iron soft magnetic composite materials prepared in Examples 11 to 15 and Comparative Example 3 are shown in Table 3.
[0119]
[0120] Table 3
[0121] In the description of the present invention, each embodiment focuses on the differences from other embodiments, and the same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part description.
[0122] In the description of the present invention, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically limited. Moreover, the term "includes", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not clearly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements limited by the sentence "comprising one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements.
[0123] In the present invention, unless otherwise clearly specified and limited, when a first feature is “on” or “below” a second feature, it may be that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, when a first feature is “above”, “above” or “above” a second feature, it may be that the first feature is directly above or obliquely above the second feature, or it may simply mean that the first feature is higher in level than the second feature. When a first feature is “below”, “below” or “below” a second feature, it may be that the first feature is directly below or obliquely below the second feature, or it may simply mean that the first feature is lower in level than the second feature.
[0124] In the description of this specification, the description of the terms "one embodiment", "some embodiments", "embodiment", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0125] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may alter, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a high-frequency, low-iron-loss soft magnetic composite material, characterized in that: The method comprises: After placing the iron-based soft magnetic powder and the coupling agent in anhydrous ethanol and stirring, the iron-based soft magnetic powder is separated and dried; After placing the iron-based soft magnetic powder and the oxide precursor in deionized water and stirring, the iron-based soft magnetic powder is separated and dried to obtain an iron-based soft magnetic powder having a coupling agent coating layer and an oxide precursor coating layer; The iron-based soft magnetic powder having the coupling agent coating layer and the oxide precursor coating layer is subjected to segmented annealing to obtain the iron-based soft magnetic powder having the coupling layer and the oxide coating layer; The iron-based soft magnetic powder having a coupling layer and an oxide coating layer, a binder, phosphoric acid or a phosphate are placed in an acetone reagent, stirred, and then dried to obtain an iron-based soft magnetic powder having a multi-layer coating structure on the surface; The iron-based soft magnetic powder with a multi-layer surface coating structure is pressed into a shape, and annealed in sections in a protective gas atmosphere to obtain a high-frequency and low-iron-loss soft magnetic composite material; The annealing process route of the stepwise annealing is: controlling the temperature at 200-300°C and keeping it warm for 30-60 minutes, adjusting the temperature at 300-450°C and keeping it warm for 30-60 minutes, adjusting the temperature at 450-600°C and keeping it warm for 60-120 minutes, and further adjusting the temperature at 600-900°C and keeping it warm for 60-120 minutes; The mass percentages of the iron-based soft magnetic powder, the coupling agent, the oxide precursor, the phosphate and the binder are: 1: (0.5%~3%): (0.1%~2%): (0.1%~1%): (0.5%~4%); The oxide precursor is at least one of zirconium oxychloride, ferric oxide, sodium hydroxide, magnesium chloride and magnesium nitrate; The phosphate is one of sodium dihydrogen phosphate, aluminum dihydrogen phosphate, potassium dihydrogen phosphate, and calcium dihydrogen phosphate.
2. The method for preparing a high-frequency, low-iron-loss soft magnetic composite material according to claim 1, characterized in that: The mass percentages of the iron-based soft magnetic powder, the anhydrous ethanol and the deionized water are: 1: (10%-20%): (50%-200%).
3. The method for preparing a high-frequency, low iron loss soft magnetic composite material according to claim 1, characterized in that: The adhesive is one of modified silicone resin, epoxy resin, polyimide adhesive and polyurethane adhesive.
4. The method for preparing a high-frequency, low-iron-loss soft magnetic composite material according to claim 1, characterized in that: The iron-based soft magnetic powder is at least one of FeNi, FeSiB, FeSi, FeSiAl, FeSiNbBCu, FeSiCr and FeSiBCrC.
5. The method for preparing a high-frequency, low-iron-loss soft magnetic composite material according to claim 1, characterized in that: The coupling agent is at least one of DL602, KH792, KH550 and KH570.
6. A high-frequency, low iron loss soft magnetic composite material, prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Formed catalyst for selective oxidation of n-butane and preparation method thereof
CN115888776A
Method for improving graphite's surface property using chemical vapor response
KR100760336B1